AR Temple Explorer: Development of Augmented Reality Mobile Application Based on Historical Building ‘Johor Ancient Temple’ - Chiew, Mei Chun; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2024)
Augmented Reality (AR) technology is widely used in tourism to enhance the tourist experience by providing an interactive and informative digital overlay on real-world attractions. However, the existing approaches often lead to limited engagement because these traditional methods can fall short of delivering an immersive experience and the lack of multilanguage support limits access to the temple’s cultural history. Hence, this project is proposed to develop an AR mobile application called AR Temple Explorer that helps anyone interested in history and culture exploring temple to know the story of the Johor Ancient Temple in a creative way. The Multimedia Mobile Content Development (MMCD) model is used for the proposed application. Functional testing and user acceptance testing have been conducted to evaluate the functionality and usability of the final developed application. Based on the System Usability Scale, an average score of 78.17% is presented to show that the developed application is highly acceptable. As a result, this project can be concluded that AR Temple Explorer is suitable for enhancing the engagement and educational experience of visitors to the Johor Ancient Temple.